Identificação de macro causas dos eventos perigosos para a proposição de medidas de controle nos planos de segurança da água (PSAs) - Dantas, Angela Di Bernardo; Di Bernardo, Luiz; Santos, Leonardo Vaz Galvão dos; Marque, Mário Berni de; Conceição, Natalia Ribeiro da; Killer, Natalia Aparecida (International Workshop for Innovation in Safe Drinking Water, 2022)
The Water Safety Planning developed by the World Health Organization (WHO), is a document in which all hazardous events and their associated hazards must be listed and given a score according to their frequency of occurency and severity, by a risk assessment approach. For the most critical problems (those with the highest scores), control measures must be proposed. So as to achieve assertive control measures, Hidrosan has created and defined the so-called macro causes (external to the water supply system, infrastructural, operational, and related to the standard operational processes) associated with each of the identified hazardous events.